Chronique juridique : jugements récents - Moreau, Rémi (Assurances, 1986)
Following our last publication of January 1986, the author continues to briefly comment on certain lawsuits published in Jurisprudence Express in 1985. This summary, intented for the broker or layman, does not aim to give full details of the lawsuits examined; rather it focuses on the main facts and the sentence rendered. This article as a work tool which may prove useful in helping readers understand the sentence and its ramifications.